The Swing Voter's Curse in the Laboratory - BATTAGLINI, MARCO; MORTON, REBECCA B.; PALFREY, THOMAS R. (Review of Economic Studies, 2009)
This paper reports the first laboratory study of the swing voter's curse and provides insights on the larger theoretical and empirical literature on “pivotal voter” models. Our experiment controls for different information levels of voters, as well as the size of the electorate, the distribution of preferences and other theoretically relevant parameters. The design varies the share of partisan voters and the prior belief about a payoff relevant state of the world. Our results support the equilibrium predictions of the Feddersen-Pesendorfer model. The voters act as if they are aware of the swing voter's curse and adjust their behaviour to compensate. While the compensation is not complete and there is some heterogeneity in individual behaviour, we find that aggregate outcomes, such as efficiency, turnout and margin of victory, closely track the theoretical predictions.